Development of a new protocol for rapid bacterial identification and susceptibility testing directly from urine samples. (June 2016) - Zboromyrska, Y.; Rubio, E.; Alejo, I.; Vergara, A.; Mons, A.; Campo, I.; Bosch, J.; Marco, F.; Vila, J.
Abstract: The current gold standard method for the diagnosis of urinary tract infections (UTI) is urine culture that requires 18–48 h for the identification of the causative microorganisms and an additional 24 h until the results of antimicrobial susceptibility testing (AST) are available. The aim of this study was to shorten the time of urine sample processing by a combination of flow cytometry for screening and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) for bacterial identification followed by AST directly from urine. The study was divided into two parts. During the first part, 675 urine samples were processed by a flow cytometry device and a cut-off value of bacterial count was determined to select samples for direct identification by MALDI-TOF-MS at ≥5 × 10 6 bacteria/mL. During the second part, 163 of 1029 processed samples reached the cut-off value. The sample preparation protocol for direct identification included two centrifugation and two washing steps. Direct AST was performed by the disc diffusion method if a reliable direct identification was obtained. Direct MALDI-TOF-MS identification was performed in 140 urine samples; 125 of the samples were positive by urine culture, 12 were contaminated and 3 were negative. Reliable direct identification was obtained in 108 (86.4%) of the 125 positive samples. AST was performed in 102 identified samples, and the results were fully concordant with the routine method among 83 monomicrobial infections. In conclusion, the turnaround time of the protocol described to diagnose UTI was about 1 h for microbial identification and 18–24 h for AST.